FORMATION OF STUDENTS' KNOWLEDGE ACTIVITY ON THE BASIS OF NATIONAL CULTURAL HERITAGE - Boykuzieva Rano Karimovna (Web of Journals Publishing, 2023)
This article talks about the problems of implementing the modern requirements for the formation of the spiritual and moral culture of a person, its connection with the development of the social system, its emergence as a result of cultural and humanitarian activities, in the process of material and spiritual activities of people.
Keywords: Personality, spiritual and moral culture, dynamic character, social system, philosophy, ethnography, ethics, aesthetics, Culture.